Inside the Mind Reader's Tool Kit Projection and Stereotyping in Mental State Inference. [article]. - Ames, Daniel R.
Mental state inferences - judgments about what others think, want, and feel - are central to social life. Models of "mind reading" have considered main effects, including social projection and stereotyping, but have not specified the conditions that govern when tese tools will be used. This article develops such a model, claiming that when perceivers assume an initial general sence of similarity to a target, they engage in greater projection and less stereotyping. Three studies featuring manipulations of similarity support this claim. Moreover, reaction time results shed light on the mechanisms underlying these effects. The proposed model gives a new view of mind reader's tool kit and, more generally, raises questions about moderators of streotyping and projection in social judgment. -- (from the author)